Evaluation of clinical efficacy of Tiletamine and Zolazepam in combination with Xylazine or Dexmedetomidine in Butorphanol and Atropine premedicated dogs for performing surgical procedures - MAHANTESH, VIJAYA; SINGLA, AMIT KUMAR; KUMAR, ROHIT; SHARMA, ANJALI; KAUSHAL, SARA; THAKUR, KALPANA; RANA, YUDHVIR; SHARMA, DEEPTI; KUMAR, ADARSH; TYAGI, S P (The Indian Journal of Animal Sciences, 2024)
A study was conducted for the clinical evaluation of Tiletamine-zolazepam when used in combination with inj. atropine, inj. butorphanol and either xylazine or dexmedetomidine in 18 client owned dogs presented for ovariohysterectomy. They were divided into two groups: group 1 (n=9) and in group 2 (n=9). The drug regime for groups included inj. butorphanol @ 0.2 mg/kg and inj. atropine @ 0.04 mg/kg followed by inj. xylazine @ 1.0 mg/kg along with tiletamine-zolazepam @ 3.3 mg/kg in group 1 and dexmedetomidine @ 10 µg/kg along with tiletamine-zolazepam @ 4.5 mg/kg in group 2. Animals in both the groups showed smooth induction with adequate muscle relaxation and analgesia. Significant decrease in rectal temperature was noticed in both the groups, which improved during recovery. ECG parameters did not show significant difference from physiological values in majority of animals. Significant increase in heart rate was noticed after induction in both groups, which came back to normal resting values at the end of the study period. Non-invasive blood pressure showed non-significant increase in both the groups initially and later dropped lower than pre-anesthetic value. SpO2, EtCO2 and FiCO2 values remained within the normal range throughout the procedure. Significant decrease in respiration rate was noticed in both groups with no incidence of apnea. Haematological parameters reduced non-significantly at the end of the study period when compared with baseline value in both the groups. Biochemical parameters and electrolytes did not vary significantly throughout the study period except for glucose which showed a significant increase throughout the study in both the groups. Recovery period was longer in group 2. Vocalization with ataxia and head bobbing was noticed in some animals of group 1 and 2 which ended after recovery without any adverse consequences. The protocol used in the study provided safe and adequate anaesthesia for different surgical manipulations that can be performed under 60 min in dogs.